2019
DOI: 10.1186/s13287-019-1394-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrillar cellulose wound dressing supports the growth and characteristics of human mesenchymal stem/stromal cells without cell adhesion coatings

Abstract: Background: In the field of regenerative medicine, delivery of human adipose-derived mesenchymal stem/stromal cells (hASCs) has shown great promise to promote wound healing. However, a hostile environment of the injured tissue has shown considerably to limit the survival rate of the transplanted cells, and thus, to improve the cell survival and retention towards successful cell transplantation, an optimal cell scaffold is required. The objective of this study was to evaluate the potential use of wood-derived n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…11,14,15 The application of CNFs as a wound dressing has also recently reached the clinical evaluation phase, 16 has been examined as a promising scaffold under in vitro conditions. 9,17,18 There are two common chemical modifications that change the charge of the cellulose chain: (1) grafting of anionic 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) oxidation 19 and (2) grafting of cationic glycidyltrimethylammonium chloride (GTMAC). 6 The benefit of these modifications is in adjusting the desired surface properties of CNFs, e.g., for controlled adsorption of bioactive molecules, which can be further stabilized by cross-linking, driven by chemical functional groups introduced into the cellulose molecule.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14,15 The application of CNFs as a wound dressing has also recently reached the clinical evaluation phase, 16 has been examined as a promising scaffold under in vitro conditions. 9,17,18 There are two common chemical modifications that change the charge of the cellulose chain: (1) grafting of anionic 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) oxidation 19 and (2) grafting of cationic glycidyltrimethylammonium chloride (GTMAC). 6 The benefit of these modifications is in adjusting the desired surface properties of CNFs, e.g., for controlled adsorption of bioactive molecules, which can be further stabilized by cross-linking, driven by chemical functional groups introduced into the cellulose molecule.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the cell–surface interactions, the CNF surface can be chemically modified to adjust the hydrophilicity or the surface charge, depending on the requirements of different cell types. It has been reported that the modifications of CNFs with cationic or anionic functional groups promoted cell adhesion, proliferation, , cytocompatibility, , cell growth directionality, water solubility, and bonding of other bioactive molecules, such as collagen and other peptides and proteins . The beneficial effect of CNF hydrogels is especially emphasized in three-dimensional (3D) cell cultivation. ,, The application of CNFs as a wound dressing has also recently reached the clinical evaluation phase, and it has been examined as a promising scaffold under in vitro conditions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Nanocellulose is biocompatible and nontoxic. Nanocellulose consists of fibers with at least one dimension in nanoscale . This makes NFC a suitable candidate for in vitro cell studies as NFC mimics the ECM which promotes the cell growth. This together with the ability to form highly porous structures makes nanocellulose a promising candidate for the fabrication of lightweight 3D structures, films, and membrane and its properties can be easily processed in the aqueous state …”
Section: Results and Discussionmentioning
confidence: 99%
“…Kiiskinen et al (2019) demonstrated the potential use of wood-derived nanofibrillar cellulose (NFC) as a wound dressing and cell scaffolding material for ASCs. The authors developed an animal-derived component-free cell transplantation method for wound care [ 58 ]. This study proved to be innovative in developing a biotechnological dressing that allowed the adhesion of MSCs and did not interfere with their cell viability and function.…”
Section: Discussionmentioning
confidence: 99%